Drivers of consumer purchase intentions for remanufactured products: A study of Indian consumers relocated to the USA. Issue 1 (12th January 2015) - Gaur, Jighyasu; Amini, Mehdi; Banerjee, Pratyush; Gupta, Ritu
Abstract : Purpose: – The purpose of this study is to understand whether being relocated to a society where remanufactured products are promoted can change consumers' perception towards them. Also, the authors wish to identify major underlying factors for remanufactured product purchase intentions. There is strong evidence in the literature that factors such as societal norms, price, age, income, education level, and availability can have significant influence on the behavioral intentions of consumers. Design/methodology/approach: – The nature of the study is to draw an embedded theory from data itself. To explore the research questions in this study, a grounded theory was used. The authors use a theoretical sampling technique and interviewed 45 India-born consumers residing in the USA for at least a period of more than six months. Findings: – The results indicate that the level of environmental consciousness, individual values, post-use perceptions, nature of purchase and socio-cultural norms are the major drivers of consumer purchase intentions. Sub-categories of these five drivers are personal and contextual factors. Personal factors include personal attitudes and beliefs, individual personality and environmental consciousness. Contextual factors are societal norms, price, promotion/advertisement, service quality and brand image. Social implications: – Use of remanufactured products is one of the ways to achieve sustainability. It is not only an environmentally friendly but also cost-effective approach. Given the major drivers identified through this study, firms can focus some on these drivers to improve their carbon footprint and bottom line. Originality/value: – This study is first to consider the decision-making process of consumer purchase of remanufactured products. In this regard, our study offers some understanding of the entire process through an action diagram.